SUN-402 Iatrogenic Cushing's Syndrome following Epidural Steroid Injections in an HIV-Infected Patient on Treatment with Genvoya - Mathias, Priyanka (J Endocr Soc, 2019)
Introduction: We report the first known case of iatrogenic Cushing's syndrome in a patient with concomitant use of epidural triamcinolone injections and Genvoya therapy for HIV. Clinical Case: A 76-year-old female with HIV and diabetes presented with two months of fatigue, 6lb weight loss, and uncontrolled hyperglycemia. Her HIV-RNA level was suppressed on Genvoya, a four-drug combination of elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide.(1) She had received four 80 mg epidural triamcinolone acetonide injections six months apart for chronic back pain starting 18 months before admission. The most recent injection was one month before presentation. She reported fatigue, depressed mood and difficulty ambulating. Examination was notable for plethoric moon facies, proximal muscle weakness, and episodic hypotension. Endocrine evaluation revealed evidence of hypothalamic-pituitary-adrenal (HPA) axis suppression with a low morning cortisol level of 4.5 mcg/dL (5-25 mcg/dL); repeat testing was undetectable at 0.8 mcg/dL. Response to Cosyntropin stimulation was adequate (cortisol 17.8 mcg/dL at 60 minutes). A urine synthetic glucocorticoid panel showed an elevated triamcinolone acetonide level of 0.69 mcg/dL (cutoff value 0.10, Mayo Medical Labs, MN). We hypothesized that the interaction between Genvoya and triamcinolone led to iatrogenic Cushing's syndrome with suppression of her endogenous HPA axis, via the inhibition of steroid metabolism by Cobicistat, a hepatic CYP3A4 inhibitor. By applying the Naranjo Nomogram for Causality and the Drug Interaction Probability Scale to this interaction, we estimated a score of 5 (probable) and 6 (probable), respectively. Her antiretroviral medication was changed to emtricitabine, tenofovir alafenamide, and dolutegravir. She was started on maintenance hydrocortisone to prevent an adrenal crisis, with immediate improvement in fatigue, muscle weakness, and improved ambulation. A repeat urine glucocorticoid panel, within three days of her HIV regimen being changed, showed a decrease in triamcinolone levels to 0.32 mcg/dL. Conclusion: Cobicistat, a CYP3A4 inhibitor, can potentiate pharmacokinetic drug interactions with the concurrent use of other medications metabolized via this pathway. A literature review revealed a single case report of adrenal insufficiency following triamcinolone injections while on the HIV medication Stribild, which also contains cobiscistat.(2) To our knowledge, there are no prior reports of Cushing's syndrome with Genvoya and exogenous steroids. We aim to increase awareness of this potential interaction to avoid adverse effects in patients on Genvoya also receiving corticosteroids. References: 1. Available at: https://www.accessdata.fda.gov/drugsatfda_docs/label/2015/207561s000lbl.pdf. Accessed: November 3, 2019. 2. J Int Assoc Provid AIDS Care. 2017 Nov/Dec;16:535-539